Comparing Union and Nonunion Establishments in Britain - Beaumont, Phillip; Harris, Richard (Relations industrielles / Industrial Relations, 1995)
Existing survey research in Britain has shown that there are notable differences between the characteristics of union and nonunion establishments. But at the same time case study research has indicated that the characteristics and employment practices of nonunion organizations vary quite widely. In order to try to reconcile these findings, this paper presents an analysis of some data contained in the 1990 national Workplace Industrial Relations Survey. The findings reveal that a sizeable minority of nonunion establisments have similar characteristics to unionized establishments which, in turn, make them particularly vulnerable to union organizing efforts and help account for the fact that it is these nonunion establishments which are most strongly opposed to a possible union presence. The implications of these findings for future research are then discussed.